Histology & Cell Biology - Burns, E. Robert Cave, M. Donald (Mosby's success in medicine., Course review., 1996)
This histology and cell biology review package (text and disk) is aimed at medical students preparing for exams. The text includes tables, lists and charts, along with 100-150 questions and answers. The accompanying disk provides another 500 questions and answers.